2010
DOI: 10.4238/vol9-2gmr836
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the AZFc region due to a human Y-chromosome microdeletion in infertile male patients

Abstract: ABSTRACT. Infertility is a major reproductive health threat; the frequency of male infertility due to Y-chromosome microdeletions is 13-18% in the human population; these microdeletions involve recurrent loss of three non-overlapping regions designated as AZFa, AZFb and AZFc, associated with spermatogenic failure. Several contradictory reports have been published regarding deletion frequency based on sequence-tagged site markers and genotypephenotype correlation. We examined the prevalence of Yq-deletion in 64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 31 publications
(31 reference statements)
1
14
0
3
Order By: Relevance
“…AZF can be further subdivided into 3 regions, including AZFa, AZFb, and AZFc. Each region contains several candidate genes involved in different stages of spermiogenesis, and deletions or mutations in these genes may cause spermatogenesis disorder, resulting in oligozoospermia or azoospermia (Pandey et al, 2010). In addition, some scholars identified a region known as AZFd between AZFb and AZFc (Kent-First et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…AZF can be further subdivided into 3 regions, including AZFa, AZFb, and AZFc. Each region contains several candidate genes involved in different stages of spermiogenesis, and deletions or mutations in these genes may cause spermatogenesis disorder, resulting in oligozoospermia or azoospermia (Pandey et al, 2010). In addition, some scholars identified a region known as AZFd between AZFb and AZFc (Kent-First et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Its etiopathogenesis is not well understood, however, it's known the importance of the role of microdeletion of subregions of the Ychromosome in the casuistry. The literature indicates that deletion of AZF, especially AZFc [12,19,32], is related to azoospermia [1,5,10,18,21,26,31,35], oligozoospermia [10,18,21,31,36] , infertility [4,24] or even normal fertility [7]. The absence of other loci is also underlined by the evidence: AZFa, AZFb, AZFd [10,20,21,23,25,29] and although the prevalence rates are not equidistant.…”
Section: Final Considerationsmentioning
confidence: 93%
“…However, Pandey et al [24] show that hormonal levels (FSH, LH and testosterone) showed significantly higher (P <0.001) in relation to controls, when evaluated 64 men with infertility, of which 3% were in AZFc microdeletion. São Pedro et.…”
Section: Y-chromosome Microdeletion: Some Histological and Physiologimentioning
confidence: 99%
See 2 more Smart Citations